MEMAHAMI ANAK DENGAN GANGGUAN PEMUSATAN PERHATIAN/HIPERAKTIF (GPP/H) DALAM SETTING SEKOLAH: attention deficit/hyperactivity disorder, children in school, functional analysis - Moesarofah Moesarofah (Buana Pendidikan, 2011)
Attention deficit/hyperactivity disorder is a developmental disorder in children with failure to meet early development tasks. Its symptoms appears before age 7 years, the cause of them predominantly influenced the neurobiological disorder, in addition to interaction with environmental factors. Core characteristics of attention deficit/hyperactivity disorder in children are characterized by the development that do not fit in focusing/inattention, hyperactivity and impulsivity. They generally appear with other accompanying problems such as learning disabilities, emotional and behavioral problems. Writing this article aimed at outlining the psychological dynamics experienced by children with attention deficit/hyperactivity disorder, as well as assess the functional analysis of the learning difficulties experienced.